Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.3390/en15020485
|View full text |Cite
|
Sign up to set email alerts
|

Instrumental Methods for Cage Occupancy Estimation of Gas Hydrate

Abstract: Studies revealed that gas hydrate cages, especially small cages, are incompletely filled with guest gas molecules, primarily associated with pressure and gas composition. The ratio of hydrate cages occupied by guest molecules, defined as cage occupancy, is a critical parameter to estimate the resource amount of a natural gas hydrate reservoir and evaluate the storage capacity of methane or hydrogen hydrate as an energy storage medium and carbon dioxide hydrate as a carbon sequestration matrix. As the result, m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 149 publications
(205 reference statements)
3
13
0
Order By: Relevance
“…First of all, it is investigated how the gas molecules are distributed among the individual cavities of the hydrate structure. Experimentally, it was observed that there is always only one single methane molecule in a cavity at most and double or multiple occupancies did not occur [53]. To explain this observation, for both the large and small cavities in the sI and sII structures, the total energies were compared for a hydrate structure with two methane molecules.…”
Section: Resultsmentioning
confidence: 99%
“…First of all, it is investigated how the gas molecules are distributed among the individual cavities of the hydrate structure. Experimentally, it was observed that there is always only one single methane molecule in a cavity at most and double or multiple occupancies did not occur [53]. To explain this observation, for both the large and small cavities in the sI and sII structures, the total energies were compared for a hydrate structure with two methane molecules.…”
Section: Resultsmentioning
confidence: 99%
“…To compare the intensity of CO 2 Raman peaks in the hydrate phase, the intensity of the CO 2 peak at any given time was normalized using eq 1, which was reported in the literature. 29 where Δn H is the amount of CO 2 consumed at time t, n g,0 is the amount of CO 2 in the gas phase at time 0, n g,t is the amount of CO 2 remaining in the gas phase at time t, and n w is the amount of deionized water used in the solution. P and T are the pressure and temperature of the gas phase in the reactor, respectively, V is the volume of the gas phase, R is the ideal gas constant, and Z is the gas compressibility calculated by the Pitzer correlation as follows.…”
Section: Methodology 241 Normalized Co 2 Raman Peak Intensitymentioning
confidence: 99%
“…To compare the intensity of CO 2 Raman peaks in the hydrate phase, the intensity of the CO 2 peak at any given time was normalized using eq , which was reported in the literature I = S normalC normalO 2 / S TB normalA + …”
Section: Methodsmentioning
confidence: 99%
“…Hydrate cavities cannot be completely filled by guest molecules, particularly small cavities. 23 The occupancy, defined as the ratio of hydrate cavities occupied by gas molecules, is a critical role, for example, in estimating the resource amount of NGHs and evaluating the gas storage and sequestration capability. The Raman spectrum technology has been extensively used to obtain the guest occupancy.…”
Section: Determination Of Hydrate Compositionsmentioning
confidence: 99%
“…Until today, gas hydrates have been studied for almost 200 years and have been shown to be useful as not only a carrier for energy storage and transportation but also a medium for gas separation and desalination. , The structure, composition, cage occupancy of gas hydrates, and kinetics of hydrate formation and dissociation are crucial in flow assurance and the applications mentioned above. Measurement technologies for microscopically characterizing and analyzing gas hydrate are gradually focused, for example, nuclear magnetic resonance (NMR) technology, infrared (IR) spectroscopy, X-ray diffraction (XRD), in situ Raman spectroscopy, etc. These spectroscopy technologies can provide in situ information on the investigated gas hydrates.…”
Section: Introductionmentioning
confidence: 99%